Legal Representation Data, 1970 - Nagel, Stuart S. ([Verlag nicht ermittelbar], 1984)
This data collection contains legal representation information gathered in a 1970 survey of 474 attorneys across the United States, which garnered 221 usable responses. The research objectives included: (1) determining the relationship between the behavior of the attorneys in representing indigent or unpopular clients and the attitudes, specialties, backgrounds, and environments of the attorneys, (2) arriving at some policy recommendations for increasing the representation of indigent and unpopular clients, and (3) analyzing the joint causation phenomenon whereby neither favorable attitudes nor favorable opportunities alone lead to representation of the unpopular, but the combination of both together does so substantially. Survey information gathered includes respondents' attitudes toward: (1) the legal profession, (2) unpopular or indigent clients, (3) sociopolitical issues regarding the poor, and (4) the system of legal representation. Respondents were asked for their experiences when representing unpopular or indigent clients and to give reasons they might not choose to represent such clients. Background information includes characteristics of the respondent's community as well as respondent's race, gender, natality, father's occupation, political party affiliation, political offices held, religious preference, type of practice, and percent of clients from ethnic and racial minorities.